Audit Committee and Financial Performance in Jordan:The Moderating Effect of Ownership Concentration - Saddam Ali Shatnawi; Mustafa Mohd Hanefah; Ahmad Marei; Monther Eldaia; Saad Alaaraj (ELIT - Economic Laboratory for Transition Research, 2024)
Indexed by WOS/SCOPUS/ERA